Total synthesis of natural fregenedadiol and its diacetate, rearranged labdanes with aromatized B ring - Philkhana, Satish Chandra; Reddy, D. Srinivasa (Tetrahedron Letters, 2017)
Labdane based natural products are most abundant and widely distributed in nature with many compounds exhibiting exceptional biological properties. Fregenedadiol is a bicyclic diterpene isolated from Halimium viscosum and represents a new carbon skeleton fregenedane with its B ring aromatized. Here, we report a total synthesis of this interesting natural product using one-pot Diels-Alder/aromatization sequence and selective hydrogenolysis as key steps. (C) 2017 Elsevier Ltd. All rights reserved.